EFEKTIVITAS PENGGUNAAN E-BOOKLET KONSEP SISTEM REPRODUKSI MANUSIA TERHADAP HASIL BELAJAR SISWA SMA - Astuti, Fuji; Noorhidayati, Noorhidayati; Halang, Bunda (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
A teacher must be able to give engaging learning tools as technology advances to keep students engaged and prevent quickly becoming bored while studying. Since it may enhance classroom instruction and boost student comprehension to accomplish learning objectives, the use of proper teaching materials can have an impact on the quality of learning. This study intends to evaluate and report the results of students' cognitive, emotional, and psychomotor learning when they acquire the idea of the human reproductive system through the use of e-booklets. The research sample was XI MIPA high school students with the research method of Pseudo Experiment. According to the study's findings, employing e-books had an impact on the outcomes of product cognitive learning at the first and second sessions. E-booklets improve cognitive learning outcomes in experimental classrooms more than in control classes. The usage of e-booklets has a good to exceptional category impact on emotional and psychomotor learning outcomes. This demonstrates that using e-booklets as teaching resources is successful in enhancing student learning results.